2014
DOI: 10.1108/jfmm-09-2012-0057
|View full text |Cite
|
Sign up to set email alerts
|

Consumer style inventory and intent to social shop online for apparel using social networking sites

Abstract: Purpose – The purpose of this paper are to examine: first, whether the consumer style inventory (CSI) consumer decision-making styles were related to opinion seeking using electronic word of mouth (eWOM) in social networking sites (SNSs) and attitudes toward online social shopping using SNSs; and second, whether opinion seeking in SNSs and attitudes mediated the links between decision-making styles and intent to social shop online for apparel using SNSs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 42 publications
3
50
0
Order By: Relevance
“…Kang et al (2014) demonstrated that novelty conscious SNS users were likely to have a favorable attitude toward online social shopping using SNSs. In addition, Mowen et al (2007) found that consumers who were open to experience were likely to ask other people for information about products, places to shop, or sales.…”
Section: Elemental Traits: Openness To Experiencementioning
confidence: 98%
See 3 more Smart Citations
“…Kang et al (2014) demonstrated that novelty conscious SNS users were likely to have a favorable attitude toward online social shopping using SNSs. In addition, Mowen et al (2007) found that consumers who were open to experience were likely to ask other people for information about products, places to shop, or sales.…”
Section: Elemental Traits: Openness To Experiencementioning
confidence: 98%
“…In the online social shopping context, Dennis et al (2010) found that value-conscious (i.e., utilitarian) shoppers mentioned price and discount comparisons as advantages of social shopping web sites. Kang et al (2014) demonstrated that price consciousness was related to attitude toward online social shopping using SNSs. Thus, consumers who are value conscious may be likely to use online social shopping for the purpose of socialization and information gratification and may intend to engage in online social shopping.…”
Section: Situational Traits: Socializing and Information-seeking Gratmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies related to professions, roles, and styles have included the shopping styles of consumers (Kang, Kim, & Wu, 2014;Mokhlis, 2010), the teaching styles of teachers (Quiamzade, Mugny, & Falomir-Pichastor, 2009;Zhang, 2009), the leadership styles of organization managers (Vinkenburg, van Engen, Eagly, & Johannesen-Schmidt, 2011;Clark, Hartline, & Jones, 2009), and the parenting styles of parents (Bastaits, Ponnet, Van Peer, & Mortelmans, 2015). Past studies have shown that people display diverse styles according to various ways of utilizing their wisdom, and they adapt their styles according to their professions, roles, and work tasks or contents, so that they can be in line with their identity and meet the requirements of their job and role (Sternberg, 1994).…”
Section: Stylementioning
confidence: 99%